THE EFFECT OF DIFFERENT TB DRUGS AND ANTIMICROBIAL AGENTS ON THE EFFICIENCY OF TREATMENT OF TUBERCULOSIS PATIENTS WITH MULTIPLE DRUG RESISTANCE - I. A. Vasilyeva; A. G. Samoylova; O. V. Lovacheva; L. N. Chernousova; T. R. Bagdasaryan (Туберкулез и болезни лёгких, 2017)
Objective of the study: to study the effect of specific TB drugs and antimicrobial agents constituting chemotherapy regimens on the efficiency of treatment of tuberculosis patients with various patterns of multiple drug resistance.Subjects and Methods. 412 pulmonary tuberculosis patients with bacillary excretion and various patterns of multiple drug resistance were enrolled into the study (117 patients with MDR TB (non pre-XDR and non-XDR); 120 patients with pre-XDR TB and 175 with XDR TB). Patients in the subgroups were compatible regarding sex and age. The patients were prescribed regimens including 5-6 drugs in accordance with their drug resistance pattern. The time of sputum conversion (by culture) versus the year of treatment was selected as a surrogate endpoint. The effect of specific TB drugs and antimicrobial agents on treatment efficiency was assessed through calculation of odds ratio (OR) of achieving a surrogate endpoint in the patients receiving and not receiving a certain drug.Results. In the subgroup of pre-XDR TB, the following drugs demonstrated the valid increase of odds of sputum conversion: ethambutol (OR 11.8), pyrazinamide (OR 10.2), moxifloxacin (OR 7.8), capreomicin (OR 4.41). Sputum conversion was achieved in all 11 patients treated with bedaquiline.In the subgroup of XDR TB, the following drugs provided a positive effect on the achievement of sputum conversion: bedaquiline (OR 9.62), linezolid (OR 8.15), cycloserine (OR 7.88), pyrazinamide (OR 7.29), moxifloxacin (OR 7.08), and ethambutol (OR 6.69). Ofloxacin demonstrated a confident negative effect on achieving sputum conversion (95% CI 0.06-0.32).